Behaviors related to physical activity and food of high school students in public educational institutions - Palacio , Diogo Queiroz Allen (2021)
The objective was to investigate the behavior of physical activity and eating habits and their relationship with the nutritional status of students. This is a cross-sectional epidemiological study with a quantitative approach. The research was carried out in six public schools located in the northeast of Brazil. The sample consisted of 1,130 students (mean age 16.6 years ± 1.1). The data collection instrument used was an objective questionnaire. The study had analytical characteristics and quantitative interpretation. Quantitative variables were expressed as mean and standard deviation. For association analyses, the chi-square test or Student's t test was used. It was considered significant p < 0.05. As a result, 64.34% of students show good nutrition (eutrophic), only 16.1% of students report achieving adequate daily consumption of fruits and vegetables and 60.1% of students are exposed to the risk of constant consumption of soft drinks. In addition, 89% of students report not reaching the minimum time of 300 minutes of weekly physical activity. Most students (73%) are actively commuting to school. Eutrophic individuals report a significantly higher prevalence of active commuting when compared to others, and 88% of students are in the group of individuals exposed to the risk of sedentary behavior. It is concluded that students show a high exposure to risks related to low consumption of fruits and vegetables and high consumption of soft drinks and fast food, an insufficient time of physical activity and a high level of sedentary behavior.